Do cash transfer programmes affect child anaemia? Results From a meta-analysis - Manley, James; Alderman, Harold (Wiley, 2025)
Childhood anaemia is common and debilitating. Nutrition-specific policies are effective for addressing anaemia in many contexts but less is known about nutrition-sensitive policies such as cash transfers. We reviewed over 4000 studies and gathered 26 estimates of the effect of cash transfer programmes on childhood haemoglobin and anaemia. Overall, neither the impact of cash on haemoglobin (0.065 d/L, CI [−0.054, 0.184]) nor on anaemia prevalence (−0.092, CI [−1.227, 1.042]) were significant. While cash on its own had basically a null effect, programmes that provided cash in combination with other interventions such as behaviour change communication or nutritional supplements were more successful. The impact of social protection on haemoglobin and anaemia is surprisingly understudied compared to height, on which a previous study found well over 100 impacts of cash transfer programmes. Overall impacts of cash transfer programmes on haemoglobin and anaemia are weak: evidence is inconclusive at best. Cash transfer programmes are more successful in combination with other programmes providing education and/or nutritional supplements.